The Philippine environment (Fighting for our world). - Paz, Cynthia C.; Papag, Ronlad; Ac-Ac, Michael; Bio, Christopher; Velasco, Federico, Jr. (Manila Ibon Foundation, 1998)
Describes the state of the Philippine ecosystems and the role transnational corporations played in environmental degradation.
IBON Video Collection.
Keywords: Environmental degradation -- Philippines; Environmental science; Philippines -- Environmental conditions